PARENTS’ AWARENESS AND PERCEPTION OF CHILDREN’S REFRACTIVE ERROR. A QUALITATIVE STUDY - Al Ghailani, Noof Ali Salim; Noushad, Babu; Khurshid, Faraz; Ismail , Galal Mohamed (Malaysian Journal of Public Health Medicine, 2020)
Uncorrected refractive error is the leading cause of moderate and severe visual impairment across the globe. An important driver for early detection and management of refractive errors among children is appropriate parental awareness. This study aims to understand the awareness and perception among parents of children with refractive errors utilizing the conceptual framework of Health Belief Model. This qualitative study focused to conduct semi-structured interviews of parents who sought eye care for their children. Thirty-five parents who visited an eye care center for refractive error correction of their children between 5 to 15 years of age were purposively selected. The four constructs of the Health Belief Model (perceived susceptibility, perceived severity, perceived benefits and perceived barriers) were applied to prepare the interview guide. The voice records of participants were transcribed verbatim, coded and qualitatively analyzed to generate relevant themes. All participants were well aware of refractive errors and the implications of them on the visual and social development of children if they leave the errors untreated. However,there were varying perception about refractive error leading to serious consequences. The enanced quality of life with proper refractive correction prompted parents to seek timely eyecare for their children.